Design of dual-band power amplifier based on tri-band impedance matching circuit. Issue 12 (13th August 2021) - Chen, H.; Liu, G.-X.; Zhu, F.; Han, M.-T.; Jiang, D.
Abstract : In this paper, a dual-band power amplifier based on tri-band impedance matching circuit is proposed. This amplifier uses reverse thinking to combine the tri-band impedance matching network with the power amplifier to mismatch the intermediate frequency as the isolation band. And the intermediate frequency is 3.0 GHz. Besides, the design process of dual-band power amplifier is given, and an example is given. Through the actual test results of the amplifier, it can be seen that the additional power efficiency of the amplifier at the frequencies of 2.6GHz and 3.4GHz is about 60%, the output power is more than 40dBm, and the gain is above 10dB. In the test results, it can be seen that the stopband of the power amplifier is 2.95-3.05GHz, the minimum gain and the minimum drain efficiency output power of the stopband are −1dB and 2%, which has a good stopband suppression effect.